Quality Improvement of Exportable Fish and Prawn through Post-Harvest Loss Reduction in Kulierchar under Participatory Stakeholder-Based Approach (Progressive Agriculture, 2013)
A participatory stakeholder-based approach was employed to improve the quality of exportable fish and prawn landed in Kulierchar of Kishoregonj through reduction of the post harvest loss and its impacts were assessed. Primary data revealed that wet fish were minimally washed with clean water immediately after harvest. Ice boxes were not used in any stages from harvest to processing plants. Bamboo split baskets were mostly used to keep or carry fish. Landed fish were found to be dispersed on plastic mat or polythene paper kept on earthen floor of the wholesaler shed, called Arat. Icing of individual catch soon after harvest was very insignificant, ranging from 2 15 % only. Prawn were found to be iced during transport to landing center at little higher rate (32%), but most of the other fish were not significantly iced during transport to landing center. Primary awareness of the beneficiaries on quality deterioration of fish was assessed and the impacts of participatory awareness development tools (PRA and RRA, personal contacts, brain storming and awareness development training) on export, income, nutrition and improved handling of landed exportable prawn/fish were re-assessed. Efficacy of such measures to improve the situation were monitored for sixteen months. Awareness in terms of benefit of good practices was high in factory technicians. Other stakeholders had very shallow or poor knowledge on use of improved handling and processing of fish. Participatory tools employed in this study was found to be effective in developing awareness of stakeholders in different value chains of wet fish handling and distribution and reducing post-harvest loss.DOI:  http://dx.doi.org/10.3329/pa.v21i1-2.16757 Progress. Agric. 21(1 & 2): 105 - 115, 2010